Spontaneous uterine rupture in primigravida at 15 weeks - Ghosh, Mousumi Das; Singh, Vinita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is a very rare and interesting case of primigravida with sonographic evidence of intrauterine pregnancy presenting with acute abdomen at 15 weeks. With the diagnosis of uterine rupture, emergency laparotomy was done. The defect was repaired and post-operative recovery was good. This shows that spontaneous uterine rupture can occur in primigravida and should be kept in mind during diagnosis of acute abdomen.